Augustine, the farmer's boy of Tagaste - Zeeuw, P. de. (Neerlandia, Alta. ; Pella, Iowa : Inheritance Publications, 1998)
A biography of Augustine of Hippo, a fourth-century teacher, whose writings had particular significance to Christians and their church at this time.
Keywords: Augustine, -- of Hippo, Saint, -- 354-430 -- Juvenile literature; Augustine, -- of Hippo, Saint, -- 354-430.; Christian saints -- Algeria -- Hippo (Extinct city) -- Biography; Saints